Therapeutic choices in patients with Ph-Positive chronic myelogenous leukemia in Mexico in the era of tyrosine kinase inhibitors: stem cell transplantation or tyrosine kinase inhibitors? Fifteen years later - Max Robles-Nasta; Daniela Sánchez-Bonilla; Moises M. Gallardo-Pérez; Edgar J. Hernández-Flores; Merittzel A. Montes-Robles; María de L. Pastelín-Martínez; Juan C. Olivares-Gazca; Guillermo J. Ruiz-Delgado; Guillermo J. Ruiz-Argüelles (Permanyer, 2024)
Background: Chronic myelogenous leukemia is a neoplastic proliferation of the granulocytic series. In Mexico, chronic myelogenous leukemia accounts for approximately 10% of all leukemias. Tyrosine-kinase inhibitors are considered front-line therapy in high-income countries, whereas allogeneic hematopoietic stem cell transplantation is a recognized therapeutic approach, mainly in low- and middle-income countries. Objective: To analyze the overall survival of persons with chronic myelogenous leukemia who have received tyrosine-kinase inhibitors or allogeneic hematopoietic stem cell transplantation in a medical center, since 1994, and briefly discuss the current indications of these treatments in the tyrosine-kinase inhibitors era. Methods: We retrospectively analyzed all patients with a diagnosis of chronic myelogenous leukemia treated in a medical center between 1994 and 2023; subsets of individuals who received an allogeneic hematopoietic stem cell transplantation or tyrosine-kinase inhibitors therapy as first-line treatment were analyzed. Results: 60 persons with chronic myelogenous leukemia were treated with allogeneic hematopoietic stem cell transplantation or tyrosine-kinase inhibitors: 35 received an allogeneic hematopoietic stem cell transplantation, whereas 25 were given tyrosine-kinase inhibitors. All patients who underwent an allogeneic hematopoietic stem cell transplantation engrafted successfully, and the procedure was completed on an outpatient basis in most cases (29/35). The median survival in allogeneic hematopoietic stem cell transplantation was 78.3 months (CI 95%: 0-205.6) and in persons given tyrosine-kinase inhibitors the median was not reached. Conclusion: Tyrosine-kinase inhibitors were significantly superior to allogeneic hematopoietic stem cell transplantation in prolonging the overall survival of persons with chronic myelogenous leukemia in our single institution experience.